ИСҲАҚХАН ИБРАТТЫҢ ИБРАТЛЫ ӨМИРИ ҲӘМ АҒАРТЫЎШЫЛЫҚ ХЫЗМЕТЛЕРИ - Сейтмуратов, Қ. (SCIENCE and SOCIETY, 2025)
The article talks about the educational-Jadid activities and pedagogical views of Ishakhon Ibrat, a famous writer-educator.
Keywords: school; Jadid school; textbook; printing house; poet; publicist; education; upbringing